Robotic Repair of a Congenital Isolated Cleft of Anterior Tricuspid Valve Leaflet. (January 2019) - Hamandi, Mohanad; Al-Azizi, Karim; Crawford, Alexander; Fan, Joy; DiMaio, J. Michael; Smith, Robert L.
Congenital isolated tricuspid valve (TV) cleft in the anterior leaflet is a rare occurrence, while clefts of the mitral valve leaflets are more common and are usually associated with other congenital heart diseases. In this article, we report a case of TV regurgitation in a young adult female due to an isolated congenital cleft in the anterior TV leaflet, which was surgically repaired using a minimally invasive robotic approach.